Technology in Second Language Education: Overcoming the Digital Divide - Lozano, Alexis Adriana; Izquierdo, Jesus (Emerging Trends in Education, 2019)
The use of information and communication technologies (ICT) can help teachers implement valuable instructional tasks where learners use the second language (L2) during input and output tasks, integrating various types of technologies, applications, and websites. Often, educational actors would argue; however, that limited access to ICT prevents teachers from implementing ICT-enhanced L2 instruction in the classroom. In this paper, we revisit that perspective through an exploration of three conditions related to the use of technologies for second language teaching: the digital divide, teacher education, and proper ICT-enhanced task implementation. Building upon a review of theoretical and empirical research on these conditions, we argue that limited access to ICT is not a determinant factor, as teacher education and careful L2 task planning can help teachers maximize the use of the limited resources available in their school contexts.